(untitled) (Bangladesh Agronomy Journal, 2020)
A pot experiment was laid down at the Department of Agronomy, Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur from November 2018 to March 2019 to improving the salinity tolerance in Foxtail millet (BARI Kaon 1) using different plant growth regulators with different doses. Two salinity levels, i) control (0mM NaCl) and ii) 80 mMNaCl were maintained after 14 days of sowing to harvest. The plant growth regulators i) Humic acid (HA): a) @ 5 gL-1 water b) @ 10 gL−1water ii) Gibberellic acid (GA3): a) @10 g L-1water b) @20 g L-1water iii) Salicylic acid (SA): a) @ 50 g L-1water b) @ 100 g L-1water were sprayed at 7 days interval from salt imposition. The experiment was in a completely randomized design (CRD) with three replications. Results revealed that plant growth regulators improved the growth and yield performance of Foxtail millet under both control and saline conditions. Amelioration of salinity tolerance in Foxtail millet was well associated with lower proline content, higher chlorophyll content and SPAD value as well as dry matter production, which facilitated the Foxtail millet yield due to application of plant growth regulators. Among the plant growth regulators, humic acid (HA) @ 5 g L-1 water was the best treatment to improving the salinity tolerance in foxtail millet under saline condition. Bangladesh Agron. J. 2019, 22(2): 25-39